1990
DOI: 10.1051/parasite/1990652051
|View full text |Cite
|
Sign up to set email alerts
|

Effets des levuresSaccharomyces boulardiisur les trophozoïtes d’Entamoeba histolytica in vitroet dans l'amibiase caecale du jeune rat

Abstract: Mémoire.Un modèle original d'amibiase caecale mis au point chez le raton a été utilisé pour étudier l'effet de la levure Saccharomyces boulardii sur le développement des lésions. Des ratons infectés par Entamoeba histolytica ont été traités par Saccharomyces boulardii ; chez les traités, le nombre de ratons malades est significativement moins élevé, la gravité de l'affection, appréciée par l'aspect macros copique du caecum et la présence d'amibes a été diminuée. Les lésions observées sont semblables à celles d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…1, 2). In vivo studies have shown that S. boulardii reduces in rats significantly the number of E. histolytica and the severity of symptoms [74]. In mice, S. boulardii reduces the number of C. albicans 20 to 50 times.…”
Section: Effect On Enteric Pathogensmentioning
confidence: 98%
See 1 more Smart Citation
“…1, 2). In vivo studies have shown that S. boulardii reduces in rats significantly the number of E. histolytica and the severity of symptoms [74]. In mice, S. boulardii reduces the number of C. albicans 20 to 50 times.…”
Section: Effect On Enteric Pathogensmentioning
confidence: 98%
“…Nevertheless, intestinal permeability to mannitol is reduced by 93% in the presence of S. boulardii. Castagliuolo et al demonstrated that the 54 kDa protease inhibits the binding of toxin A and B to their receptors on the membranes of the intestinal villi [25,26,74].…”
Section: Effect On Enteric Pathogensmentioning
confidence: 99%
“…Earlier studies showed that treatment with S. boulardii decreased mortality and morbidity in young rats infected with E. histolytica (38). CDR Sprague-Dawley young rats were infected with 5 X 10 5 trophozoites of E. histolytica and given either 1.8 X 10 9 CFU / d of S. boulardii or saline for 4 d. Rats were sacrificed on the 5th d and autopsied.…”
Section: Microbial Interactionsmentioning
confidence: 99%
“…O Lactobacillus acidophilus impede também a adesão de microorganismos patogênicos em cultura de células intestinais humanas 13 . O tratamento com Saccharomyces boulardii reduz a mortalidade de ratos jovens infectados com Entamoeba histolytica 14 . In vitro, o contato entre este protozoário e o Saccharomyces boulardii, suas membranas ou o sobrenadante de cultivo da levedura, reduz o número de trofozoitos capazes de aderir a eritrócitos 15 .…”
Section: Proteção Ecológicaunclassified